Eating more sardines instead of fish oil supplementation: Beyond omega-3 polyunsaturated fatty acids, a matrix of nutrients with cardiovascular benefits - Santos, Heitor O.; May, Theresa L.; Bueno, Allain A. (Frontiers in Nutrition, 2023)
Omega-3 polyunsaturated fatty acids (n-3 PUFA) play a significant role in the prevention and management of cardiometabolic diseases associated with a mild chronic pro-inflammatory background, including type 2 diabetes, hypertension, hypertriglyceridaemia, and fatty liver disease. The effects of n-3 PUFA supplements specifically, remain controversial regarding reducing risks of cardiovascular events. n-3 PUFA supplements come at a cost for the consumer and can result in polypharmacy for patients on pharmacotherapy. Sardines are a well-known, inexpensive source of n-3 PUFA and their consumption could reduce the need for n-3 PUFA supplementation. Moreover, sardines contain other cardioprotective nutrients, although further insights are crucial to translate a recommendation for sardine consumption into clinical practice. The present review discusses the matrix of nutrients contained in sardines which confer health benefits for cardiometabolism, beyond n-3 PUFA. Sardines contain calcium, potassium, magnesium, zinc, iron, taurine, arginine and other nutrients which together modulate mild inflammation and exacerbated oxidative stress observed in cardiovascular disease and in haemodynamic dysfunction. In a common serving of sardines, calcium, potassium, and magnesium are the minerals at higher amounts to elicit clinical benefits, whilst other nutrients are present in lower but valuable amounts. A pragmatic approach towards the consumption of such nutrients in the clinical scenario should be adopted to consider the dose–response relationship effects on physiological interactions. As most recommendations currently available are based on an indirect rationale of the physiological actions of the nutrients found in sardines, randomised clinical trials are warranted to expand the evidence on the benefits of sardine consumption.